Study guides

☆☆

Q: 6d-3d plus 2d equals 35 what is the unknown?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

To keep it balanced, whatever you do to one side of the equals, do to the other: 2d + 7 = 9 ⇒ 2d + 7 - 7 = 9 - 7 ⇒ 2d = 2 ⇒ 2d ÷ 2 = 2 ÷ 2 ⇒ d = 1

2d + 25 = 55Therefore 55 - 25 = 2dTherefore, 2d = 30d = 30/2Therefore, d = 15

4(9)-11=25 2(9)+7=25 d=9

15 ac + 20 bc + 6 ad + 8 bd =3a (5c + 2d) + 4b (5c + 2d) =(3a + 4b) (5c + 2d)

3d-3d cancel 2d-3d=-1d 8=-1d-17 -17+17 cancel 8+17=25 25=-1d 25/-1=-1d/-1 d=-25

Related questions

2d + 7 = 9 2d = 2 d = 1

10 sided 2D shape is called a decagon 20 sided 2D shape is called a icosagon 30 sided 2D shape is a swimming pool 40 sided 2D shape is unknown 50 sided 2D shape is unknown 60 sided 2d shape is unknown 70 sided 2d shape is unknown 80 sided 2d shape is unknown 90 sided 2d shape is unknown 100 sided 2d shape is unknown 110 sided 2d shape is unknown 111 sided 2d shape is unknown 120 sided 2d shape is unknown 130 sided 2d shape is unknown

To keep it balanced, whatever you do to one side of the equals, do to the other: 2d + 7 = 9 ⇒ 2d + 7 - 7 = 9 - 7 ⇒ 2d = 2 ⇒ 2d ÷ 2 = 2 ÷ 2 ⇒ d = 1

2d+1=29 2d=29-1=28 d=28/2=14

2d + 25 = 55Therefore 55 - 25 = 2dTherefore, 2d = 30d = 30/2Therefore, d = 15

-7d = 50 + 2d -9d = 50 d = -50/9 Or about -5.6

3d + 8 = 2d - 7 3d -2d = -8 - 7 1d = - 15 d = -15

I--2a+b=2c+2d II--2a+b=c+2d III--a+2b=3d * Here if we perform (I)-(II), we get, c=0 * Using the c we can prove b=0 using (I)-(III). * Now replace 'b' & 'c' as 0 in (I), then we get a=d. Email me at yash2008gates@gmail.com for any queries. I will be very thankful to receive your queries.

3d+8=2d-7 3d+8-8=2d-7-8 (substract 8 on both side) 3d=2d-15 3d-2d=2d-2d-15 (substract 2d on both side) d=-15

22d - 1

Solving for d: d = -4.7 satisfies the equation.

(-70-2+9)d + (39-75+1) = -63d -35